Reader Response: Association of Sleep, Neuropsychological Performance, and Gray Matter Volume With Glymphatic Function in Community-Dwelling Older Adults. (14th February 2023) - Piantino, Juan A.; Iliff, Jeffrey J.; Lim, Miranda M.; Levendovszky, Swati Rane
Abstract : In this article, Siow et al. 1, 2 used diffusion tensor imaging along the perivascular space (DTI-ALPS) as a marker of glymphatic function in community-dwelling older adults. We raise 4 notes of caution in interpreting the findings from studies using DTI-ALPS to measure human brain glymphatic function. First, the relationship between the DTI-ALPS index and gold standard contrast-based glymphatic imaging has not yet been rigorously defined. In addition, glymphatic exchange occurs throughout the brain volume and exhibits regional variability. The relationship between diffusion parameters at a single anatomical location and glymphatic function throughout the rest of the brain is currently unknown.